Criteria and indicators for assessing the sustainability of forest management: conservation of biodiversity - Stork, N.E.; Boyle, T.J.B.; Dale, V.; Eeley, H.; Finegan, B.; Lawes, M.; Manokaran, N.; Prabhu, Ravi; Soberon, J. (1997)
The need for new criteria and indicators for the assessment of biodiversity conservation as part of sustainable forest management of tropical forests has been identified as a priority by many international organisations. Those biodiversity criteria and indicators which formed part of a much broader initial assessment by the Center for International Forestry Research (CIFOR) (Prabhu et al. 1996) were found to be deficient. This Working Paper contains specific proposals for biodiversity criteria and indicators. These proposals originated from a workshop of experts, and are intended to be adapted and refined for use in specific situations. Criteria and indicators need to be applied at the forest management unit level and those for biodiversity are just one part of a package that includes socio-economic and other categories. Biodiversity is an extraordinarily broad concept and, given the huge diversity of life in tropical forests, it is impossible to make rapid direct assessments of biodiversity in forests in anything other than a superficial manner. It is likely that there will be limited skilled human resources and time for biodiversity assessment in any system of criteria and indicators, so it is important that we design tools that do not require expert application and interpretation. The usefulness of "indicator groups", "keystone" species and other concepts is still argued among biologists and their utility is questionable. This paper suggests that, in contrast to more traditional approaches to assessing taxonomic diversity, it may be possible to assess the effects of management practices on biodiversity by examining the state of those processes that generate or maintain biodiversity. The indicators and verifiers that we have suggested examine the state of these processes. We recommend that for each indicator, quick and easy verifiers, which we designate "Primary" verifiers are used first, and more sophisticated ("Secondary") verifiers are used only if clear results are not obtained from Primary verifiers. This paper is merely a first step in creating a suitable framework for applying a proposed a set of forest biodiversity indicators and verifiers. The framework and the indicators and verifiers require field testing, and we fully expect there to be changes resulting from the field trials, which will be reflected in major improvements in their effectiveness. For the sake of brevity we have not discussed the advantages and disadvantages of the verifiers in full. While changes are expected, the approach taken is powerful in that it recognises the relationship between interventions and consequences, and it demonstrates that some indicators are more widely valuable than others.